Pragmatic Acts in President Muhammadu Buhari’s Independence Day Speech of October 1, 2017 - Odogwu, Cynthia Nkechinyere; Akpojisheri, Monday (NIU Journal of Humanities, 2018)
Independence Day speeches are delivered in Nigeria on October 1 st annually by the President and Commander-in-chief of the Armed Forces to commemorate the day of democratic freedom from the Great Britain and freedom from all internal and external forces. President Buhari’s Independence Day speech of 2017 is of pragmatic importance because it raised plethora of issues as Nigerians read meaning based on personal judgments and opinions. Nevertheless, the speech encapsulates different pragmatic functions and it is the aim of this paper to unravel them all employing the Pragmatic Acts Theory of Mey (2001) from a descriptive quantitative perspective. The analysis of the speech revealed a preponderance of sixty-two (62) acts serving four pragmatic goals: thanking, acknowledging and remarking achieved the goal of appreciating and admitting which had a preponderance of 29%; stating, proposing and assuring achieved the goal of revealing intentions/results of his administration with a preponderance of 46.7%; reminding, instructing/calling, advising, charging, criticizing and hoping is to give directives/instructions with 19.4%. Finally, identifying and describing achieved the goal of giving details on key issues with a preponderance 12.9%. These acts were further marked by some pragmatic tools such as Shared Situation Knowledge (SSK), Psychological Act, and Relevance. This paper concludes on the note that President Buhari allayed the fears and outcries of Nigerians as he focused on key issues that bother on revamping the security and power sectors. Keywords: independence day speech, pragmatic acts, president Buhari, language and politics.